The effect of website-supported positive self-talk therapy on anxiety levels among eleventh-grade students - Silvi 'Indana Rusyida; Lailatul Fadilah; Osep Yasier Almunsiri; Alif Nurul Rosyidah (JOURNAL OF Mental Health Concerns, 2026)
Background: Anxiety in adolescents is a mental health problem that can affect the learning process, psychological development, and social relationships. Academic pressure, emotional changes, and environmental demands are factors that contribute to the emergence of anxiety in adolescents. One non-pharmacological intervention that can be used to help reduce anxiety is Positive Self-Talk Therapy. The implementation of this intervention can be supported by website media, which facilitates access to independent, continuous practice. Purpose: To find out the effect of Positive Self-Talk Therapy with the support of the website media on the anxiety level of eleventh-grade students. Method: A pre-experimental design with a one-group pre-test-post-test approach by Positive Self-Talk Therapy with the support of the website media ‘Suara Positifku’. The research sample consisted of 33 respondents selected through purposive sampling, with proportional representation in each class. Anxiety levels were measured using a teenage anxiety questionnaire that had been adapted and modified by Ways AlQorny in 2023. Results: The average level of student anxiety decreased from 21.42 before taking the intervention to 13.97 after taking the intervention. The results of the Wilcoxon Signed Rank Test showed a significance value of p < 0.001, (p < 0.05). Conclusion: Positive Self-Talk Therapy with the support of the website media has a significant effect on the anxiety levels of eleventh-grade students. Keywords: Anxiety; Positive Self-Talk Therapy; Teenagers; Website.